A higher-order sliding mode controller’s super twisting technique for a DC–DC converter in photovoltaic applications - Tushar Waghmare; Pradyumn Chaturvedi (Energy Reports, 2023)
Electricity can be produced using solar photo.voltaic (SPV) modules. Variable solar energy operational characteristics including irradiance, ambient temperature, wind speed, etc. considerably affect the output voltage and load power of SPV-based systems. DC–DC power converters create extra challenges for the robust design of power converters since they provide a constant voltage to the power line. A more robust control design for the power converter is required due to the characteristics and load patterns of a nonlinear system. This paper explains how to effectively regulate high-order sliding mode (HOSM) in solar photovoltaic isolated flyback converters. Compare the suggested HOSM approach with the usual PI control technique. The proposed HOSM control strategy outperforms conventional PI control techniques in uncertain and perturbed environments. This research also offers a unique technique for avoiding chattering in flyback converters (FCs) through the use of super-twisting sliding modes.